Ventriculoperitoneal shunt presenting as umbilical CSF fistula - Yeola (Pate), Meenakshi (J Family Med Prim Care, 2020)
An umbilical cerebrospinal fluid (CSF) fistula following a ventriculoperitoneal (VP) shunt is an extremely rare complication. The shunt can get blocked and infected and present as purulent umbilical discharge. We report an 11-month-old female infant who presented with recurrent purulent umbilical discharge, 6 months after VP shunt operation for hydrocephalus. After relevant investigations, she underwent exploratory laparotomy which revealed an umbilical CSF fistula with a blocked VP shunt. VP shunt removal was done with excision of the fistulous tract. The post-op period was uneventful and umbilical discharge ceased. She is further planned for endoscopic third ventriculostomy. Umbilical discharge in a neonate may be due to several pathologies. The family physician is the first point of contact in the majority of the cases before they seek a specialist. Hence, recurrent umbilical discharge not responding to conservative management must be evaluated carefully, referred promptly, and the underlying pathology to be treated.